Evaluation of safety practices and performance in a brewery industry in Nigeria between 2000 - 2007 (2011)
Safety practices and performance in a brewery industry in Nigeria was evaluated for a period of eight years between 2000 - 2007 using the principles of statistical expectation and efficiency index. The number of prevented accidents and the corresponding values of lives and property saved were estimated annually for the same period of eight years. The type of input resource, total number of input resources, total number or prevented accidents by class, the unit cost of each of the accident class, the cost of input resources, quantity of each type of input resources and the targeted period were identified. The study revealed that a total of 156 accidents were prevented in the period of the safety programme which translates to an average of 19.45 per year. The safety programme also saved lives and property worth N20.2 million for the eight year period which is at an average of N2.5 million annually. The computation of efficiency indices due to the use of all the input resources when compared with the standard period and it was discovered that all the resources were well utilised. The significance and benefits of the work to the local community and other industries is that the principles of statistical expectation and efficiency index can be easily applied to analyse the performance of safety programme in the industries.